Modernizing Zakat and Waqf Management in Indonesia: A Legal And Governance Perspective - Nashirudin, Muh.; Razali, Ramadhan; Ulfah, Almira Keumala (Fakultas Syariah UINSI Samarinda, 2025)
Zakat and waqf are vital tools for poverty alleviation in Islamic countries. However, their management often fails to keep pace with technological advancements, so legality and good governance cannot be seen directly by the muzakki. In Indonesia, the largest Muslim-majority country, the digitalization of zakat and waqf has emerged as a significant reform, supported by regulations to improve transparency, accountability, and efficiency. This study examines the integration of corporate governance principles in digital zakat and waqf management, focusing on the regulatory framework that governs these practices. Employing normative legal research, this study analyzes Indonesia’s Zakat Management Law (No. 23 of 2011) and the Waqf Law (No. 31 of 2004), alongside case studies of digital zakat and waqf platforms. The findings highlight that these regulations mandate technology to enhance monitoring, reporting, and fund distribution. Adopting corporate governance frameworks, including digital fundraising, real-time tracking, and performance audits, has substantially increased public trust and participation in zakat and waqf. Nevertheless, challenges remain, such as regulatory gaps in monitoring non-compliance and integrating private sector innovations. This research underscores the importance of strengthening regulatory oversight and adopting global best practices to optimize the socio-economic impact of zakat and waqf in Indonesia.